SYNTHESIS, CHARACTERIZATION AND SWELLING STUDY OF PGMA HYDROGEL BASED ON POLY (GLYCIDYL METHACRYLATE) - Souli, L; Lahrech, M.B; Djemoui, A (university of el oued/جامعة الوادي, 2018)
The PGMA hydrogel studied in this work was prepared by physical cross-linking of poly (glycidyl methacrylate) (PGMA) at 50-55°C without cross-linking agent. The PGMA was synthesized by ring opening polymerization of glycidyl methacrylate (GMA) in presence of Maghnite-H+ as an catalyst at room temperature. The PGMA hydrogel synthesized was characterized by FT-IR, by X-ray diffraction (XRD), by scanning electron microscope (SEB) and by swelling measurements. The results obtained by X-ray diffraction, showed that the PGMA hydrogel formed by two structures, a crystalline structure and an amorphous structure. Scanning electron microscopy (SEM) analysis indicated that a porous structure of PGMA hydrogel. The equilibriums water content (EWC) obtained were 74.81% at 20°C, 79.38% at 40°C and 85.81% at 60°C.
Article
Keywords: Hydrogel; physically cross-linking; poly (glycidyl methacrylate); swelling study.